(untitled) (Bangladesh Journal of Agricultural Research, 2017)
BRRI dhan52 is a uniquire submergence tolerant rice variety containing prominant genetic background of BR11, a mega rainfed lowland rice (RLR) variety of Bangladesh, but is susceptible to bacterial blight (BB) caused by Xanthomonas oryzae pv. oryzae (Xoo). The variety is considerably popular in the southern part of Bangladesh due to its high yield in flash flood condition and comparatvely medium slender grain. Molecular markers linked to BB resistance genes (Xa genes) and submergence QTL (SUB1) were utilized in a marker-aided selection program to develop elite breeding lines with broad-spectrum resistance to bacterial blight. Sequence tagged site (STS) and simple sequence repeat (SSR) markers were essentially used to detect the genes for BB and submergence as well. In backcross generation, markers closely linked to Xa21 and SUB1 QTL were used to select desirable plants possessing these resistance genes (foreground selection) and microsatellite markers polymorphic between donor and recurrent parent were also used to select plants that have maximum contribution from the recurrent parent genome (background selection). In BC1F1 generation, three best plants consiquently were selected from previously selected ten double heterozygous (Xa21 and SUB1 QTL) plants. The percentage of recipient genome recovery in the best plant 1, 2 and 3 were 78.7%, 75.83% and 75.4%, respectively. Eventually this work illustrates the successful application of marker-assisted breeding for introgression of bacterial blight resistant gene into a rice variety of Bangladesh. Bangladesh J. Agril. Res. 42(3): 403-411, September 2017